Effect of B-vitamin supplementation on nursery pig growth performance - James, B.W.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 35-d growth assay was conducted to determine the effect of added dietary B-vitamins on growth performance of nursery pigs (12.9 lb initial BW). The basal diet (Phase I, 1.5% lysine; Phase II, 1.3% lysine) was formulated to contain no added Bvitamins. The other treatment diets were formed by adding a B-vitamin premix (biotin, folacin, niacin, pantothenic acid, riboflavin, thiamin, B6, and B12) to the basal diet with the vitamins added at 1, 2, or 4 times NRC (1998) recommendations. In phase I (d 0 to 14) and for the overall trial, pigs fed increasing Bvitamins had increased (linear, P<0.04) ADFI and improved (quadratic, P<0.04) feed efficiency. Feed efficiency was best for pigs fed the diet with B-vitamins added at the NRC requirement. There was no effect of B-vitamin level (P>0.09) on growth performance in phase II (d 14 to 35). These results suggest that B-vitamin supplementation is necessary to maximize growth performance of earlyweaned pigs; however, typical margins of safety for B-vitamins can be lowered without affecting growth performance.
Keywords: B-vitamins; Growth performance; Nurstery pigs; Swine